2022
DOI: 10.1177/14799731221117298
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and impact on clinical outcomes of sarcopenia in patients with idiopathic pulmonary fibrosis

Abstract: Objectives Sarcopenia is a syndrome characterized by reduced muscle mass and function. It is well-recognized as a complication in chronic diseases such as chronic obstructive pulmonary disease. However, little is known about sarcopenia in patients with idiopathic pulmonary fibrosis (IPF). This study aimed to investigate the clinical characteristics of sarcopenia and the association between quality of life and sarcopenia in patients with IPF. Methods In this pilot cross-sectional study, 56 Japanese outpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…This might lead to increased exercise tolerance and cardiorespiratory fitness through increased oxygen consumption via increased muscle diffusion, mitochondrial respiration capacity, and skeletal muscle strength, as already proposed in patients with heart failure [ 73 , 74 ]. This hypothesis is further supported by the results of studies reporting that lower skeletal muscle mass and strength are significantly associated with advanced disease and mortality in patients with IPF [ 75 , 76 , 77 ]. Furthermore, one study in our systematic review reported a significant and positive association between BMI and the cross-sectional area of elector spine muscles, an imaging parameter used to investigate sarcopenia and cachexia.…”
Section: Discussionmentioning
confidence: 63%
“…This might lead to increased exercise tolerance and cardiorespiratory fitness through increased oxygen consumption via increased muscle diffusion, mitochondrial respiration capacity, and skeletal muscle strength, as already proposed in patients with heart failure [ 73 , 74 ]. This hypothesis is further supported by the results of studies reporting that lower skeletal muscle mass and strength are significantly associated with advanced disease and mortality in patients with IPF [ 75 , 76 , 77 ]. Furthermore, one study in our systematic review reported a significant and positive association between BMI and the cross-sectional area of elector spine muscles, an imaging parameter used to investigate sarcopenia and cachexia.…”
Section: Discussionmentioning
confidence: 63%
“…Once consented, all patients underwent a standard 8-week outpatient PR program conducted by the members of the Department of physical therapy. 16 Patients are initially evaluated by a dedicated physical therapist and are requested to be seen ideally twice weekly thereafter to partake of the program that involves upper and lower body strength and endurance training. Many patients, however, are indigent, having limited financial resources and able to come at best once a week or every other week, mainly because of transportation issues, illness, or hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…The numbers in each category were too small to achieve significant associations with pulmonary function, so larger studies are needed to demonstrate a relation as studies suggest that sarcopenia may be more severe and extensive in CAL than in ILD and have a greater effect on outcome. 13 , 14 , 15 , 16 This study was also affected by the COVID-19 pandemic during which our center experienced closures of most outpatient services including physical rehabilitation. For pragmatic reasons, most PR programs hold sessions only 2 or 3 times weekly, 20 but most programs instruct patients to exercise at home in between sessions, as we do.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations